Investigation of the wind characteristics and prospects of wind power use in Lithuania - Katinas, Vladislovas; Sankauskas, Donatas; Perednis, Eugenijus; Vaitiekūnas, Petras (Journal of Environmental Engineering and Landscape Management, 2013)
This paper addresses the current situation and future prospects of the use of wind energy in Lithuania. Furthermore, it investigates wind power resources. During the last ten years, assessment of wind power resources was carried out, wind characteristics measurements were made, observation data of Lithuanian meteorological stations were collected and these data were generalized. Measurements have shown that the most suitable and promising region for installation of wind turbines and wind farms in Lithuania is the coastal area of the Baltic Sea. The suitability of several existing wind turbine sites was evaluated according to the variation of the capacity factor C p, which describes the efficiency of installed wind turbines. Global trends in the development of the power sector reveal the prevalence of wind power installations. The increase in the use of wind energy not only reduces environmental pollution, but also creates new jobs in rural areas and decreases dependence on fossil fuels. The aim of this work is to present the current situation of wind energy development and the results of the investigation of wind climate conditions in Lithuania. The investigations demonstrated good prospects for wind power utilization at the coastal area of the Baltic Sea, as well as possibilities to install wind turbines on the continental part of Lithuania.